The Association among Childhood Trauma, Pathological Dissociation and Gambling Severity in Casino Gamblers. (21st December 2015) - Imperatori, Claudio; Innamorati, Marco; Bersani, Francesco Saverio; Imbimbo, Francesca; Pompili, Maurizio; Contardi, Anna; Farina, Benedetto
Abstract : The aim of the present study was to explore the role of pathological dissociation in mediating the association between childhood trauma (CT) and gambling severity. One hundred seventy‐one (134 men and 37 women) gamblers recruited in gambling environments (i.e., two Italian casinos) have been enrolled in the study. Psychopathological assessments included the Childhood Trauma Questionnaire (CTQ), the Dissociative Experiences Scale‐Taxon (DES‐T), the South Oaks Gambling Screen (SOGS), the CAGE and the Hospital Anxiety and Depression Scale. A mediational model, analyzing the direct and indirect effects of CTQ on SOGS through the mediating role of DES‐T, showed that the relation between CTQ and SOGS was fully mediated by DES‐T scores ( b = 0.07; se = 0.15; p < 0.001). This finding raises the possibility that CT explains gambling severity through the presence of pathological dissociative symptoms and dissociative pathogenetic processes. Copyright © 2015 John Wiley & Sons, Ltd. Key Practitioner Message: Gambling severity is associated with both childhood trauma and pathological dissociation in casino gamblers. A mediational model shows that the effect of childhood trauma on gambling severity is entirely mediated by pathological dissociation. From a clinical point of view, our results highlight the importance of assessing, and possibly treating, dissociative symptoms in individuals with gambling disorder.